2021
DOI: 10.1515/npprj-2021-0021
|View full text |Cite
|
Sign up to set email alerts
|

Application of modified cellulose nanofibrils as coating suspension on recycled paper using size press

Abstract: Cellulose based nanomaterials have the great potential to be applied to paper as bulk additive or coating material to improve overall final properties, especially in secondary fiber. In the present work, the effect of applying different kinds of cellulose nanofibrils (CNF) to papers obtained from recycled fibers using size press on physical, mechanical and barrier properties was investigated and compared with the sole use of starch as coating material. The coating process of CNF was carried out by the addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…In the same manner, Balea et al (2016) reported a 40% increase in SCT values of OCC by the bulk addition of 4.5% CNF obtained from bleached eucalyptus kraft and bleached never-dried northern pine pulps. In contrast, Fidan et al (2021) indicated that the coating application of CNF provides better SCT values than bulk addition of the same amount of CNF. The authors reported a 133.3% increase in SCT values of recycled fluting papersheet after size press application of 4% CNF.…”
Section: Crush Testsmentioning
confidence: 82%
See 3 more Smart Citations
“…In the same manner, Balea et al (2016) reported a 40% increase in SCT values of OCC by the bulk addition of 4.5% CNF obtained from bleached eucalyptus kraft and bleached never-dried northern pine pulps. In contrast, Fidan et al (2021) indicated that the coating application of CNF provides better SCT values than bulk addition of the same amount of CNF. The authors reported a 133.3% increase in SCT values of recycled fluting papersheet after size press application of 4% CNF.…”
Section: Crush Testsmentioning
confidence: 82%
“…Thus, the internal bonding ratio increased drastically. Additionally, Fidan et al (2021) noted a substantial 110.9% improvement in internal bond strength following the surface sizing of 90 g/m 2 fluting papers using CS/CNF suspensions. Similarly, Tozluoğlu and Fidan (2023) reported 119.9% increase in internal bond strength of 110 g/m 2 recycled fluting paper sheets after size press of CS+4% CNF.…”
Section: Mechanical Propertiesmentioning
confidence: 94%
See 2 more Smart Citations
“…The purpose of fractionation is to utilize long fiber fractions for high-quality products and short fiber fractions for low-grade products, or to remix the short fiber fraction with a mechanically treated long fiber fraction to improve product quality and conserve refining energy [12][13] . Although this theoretical idea is generally accurate, it may not be applicable for repeatedly recycled fibers because the changes in fiber properties, including hornification and shortening of fiber lengths accompany recycling and are aggravated by recycling times [14][15] . However, fractionation of the recycled OCC and selective treatment of these fractions Refining is a mechanical strategy to improve the bonding properties of the fibers in the pulp, which in turn improves paper properties, such as tensile strength [16][17] .…”
Section: Introductionmentioning
confidence: 99%